2019
DOI: 10.1074/jbc.ra119.009902
|View full text |Cite
|
Sign up to set email alerts
|

Conditional depletion of the RNA polymerase I subunit PAF53 reveals that it is essential for mitosis and enables identification of functional domains

Abstract: Our knowledge of the mechanism of rDNA transcription has benefited from the combined application of genetic and biochemical techniques in yeast. Nomura's laboratory (Nogi, Y.,

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(24 citation statements)
references
References 119 publications
2
22
0
Order By: Relevance
“…Studies in yeast have demonstrated that A49 can be recruited to the polymerase independently of A34. For example, the deletion of the heterodimerization domain does not affect proliferation [21,38]. However, deletion of the dimerization domain of PAF53 significantly inhibited prolifer- Interestingly, the tWH domains of TFIIE and A49 both lie upstream of the transcription initiation site, and the linker domains of TFIIF and TFIIE appear to span the polymerase cleft in a manner similar to the HTH of A49.…”
Section: The Pafs' Function As a Heterodimermentioning
confidence: 99%
See 4 more Smart Citations
“…Studies in yeast have demonstrated that A49 can be recruited to the polymerase independently of A34. For example, the deletion of the heterodimerization domain does not affect proliferation [21,38]. However, deletion of the dimerization domain of PAF53 significantly inhibited prolifer- Interestingly, the tWH domains of TFIIE and A49 both lie upstream of the transcription initiation site, and the linker domains of TFIIF and TFIIE appear to span the polymerase cleft in a manner similar to the HTH of A49.…”
Section: The Pafs' Function As a Heterodimermentioning
confidence: 99%
“…Our demonstration that PAF49 is essential for growth and transcription while its ortholog, yeast A34, is nonessential, highlights the importance of further studying Pol I transcription in mammals. [38]. Cells were treated with or without indole-3 acetic acid (IAA) for 3 h. Whole-cell extracts were prepared, and levels of PAF49 were determined via Western blot analysis.…”
Section: Are Pafs Necessary For Rdna Transcription? Cell Growth? Cell Viability?mentioning
confidence: 99%
See 3 more Smart Citations